Iz raziskav na področju latinskih zloženk - Lindner, Thomas (Keria (Ljubljana), 2003)
In the article, I am dealing with the history of Latin naominal compounds. In delineating their development from the prehistoric period to late antiquity, Iwant to disprove the ancient prejudice regarding their poor productivity. In a concluding chapter, lexicographical problems are discussed.
Keywords: antika; besedotvorje; latinščina; leksikologija; zgodovina jezika